Modula??o codificada por blocos de baixa complexidade com c?digos de comprimentos diferentes - Sim?es Junior, Rui Rodrigues (2006)
Abstract: The objective of this dissertation is to present schemes of block coded modulation using error correcting codes with different lengths for different coding levels. This proposal is a solution to obtaining good coding gains without the coding rate implying in expansion of bandwidth and hight decoding complexity. The concept proof made through computations simulations for coded QPSK over uncoded BPSK modulations in AWGN and Rayleigh channels. The scheme proposal also is compared the BCM schemes with codes of the same lengths to all the coding levels.